Answer:
a + b + c = 1
Step-by-step explanation:
To expand the bracket, [tex](2x - 3)^{2}[/tex] we will simply be multiplying the bracket by itself.
This will be the same as having [tex](2x - 3) \times (2x - 3)[/tex]
The first step in doing this is to multiply each of the values in the second bracket by the values in the first one.
[tex]2x \times 2x =4x^2[/tex]
[tex]2x\times -3 = -6x[/tex]
[tex]-3 \times 2x = -6x[/tex]
[tex]-3 \times -3 =9[/tex]
Once this is done, the next step is to group the like terms and evaluate the result.
[tex]4x^2 -6x-6x +9[/tex]
[tex]4x^2 -12x +9[/tex]
This is algebraic expression is the result of the expansion of [tex](2x - 3)^{2}[/tex] .
Based on the descending powers of x
a = 4
b = -12
c = 9
These are the coefficients of [tex]x^2[/tex] and [tex]x[/tex] and also the last figure.
a + b + c = 4 -12 +9 = 1